PERAN KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA DALAM MENINGKATKAN KINERJA KARYAWAN PADA INSPEKTORAT KEMENTERIAN KOORDINATOR BIDANG PEMBANGUNAN MANUSIA DAN KEBUDAYAAN (KEMENKO PMK) - Santoso, Bagus Iman (Jurnal Ilmiah Mahasiswa FEB, 2019)
Abstract: This study was conducted in the Coordinating Ministry of Human and Cultural Development in Jakarta. The objective is to identify the individual and simultaneous effect of transformational leadership and work motivation on employee performance. This explanatory research explains the causal relationship among the variables through hypothesis testing. Using Quota Sampling, fifty people were selected as the respondents. The instrument test and multiple linear regression were performed in SPSS 24.0. This research finds that transformational leadership influences employee performance, that work motivation influences employee performance, and that transformational leadership and work motivation simultaneously influence employee performance. Keywords: transformational leadership, work motivation, employee performance